Left ventricular remodeling and its association with mineral and bone disorder in kidney transplant recipients - Li Sun; Dongliang Zhang; Jiawen Liu; Xiang Gao; Chuanjian Suo; Shuang Fei; Zhengkai Huang; Zijie Wang; Hao Chen; Jun Tao; Zhijian Han; Xiaobing Ju; et al. (Renal Failure)
Background The assessment of left ventricular (LV) remodeling and its association with mineral and bone disorder (MBD) in kidney transplant recipients (KTRs) have not been systematically studied. We aimed to evaluate LV remodeling changes one year after kidney transplantation (KT) and identify their influencing factors.Methods Ninety-five KTRs (68 males; ages 40.2 ± 10.8 years) were followed before and one year after KT. Traditional risk factors and bone metabolism indicators were assessed. Left ventricular mass index (LVMI), left ventricular ejection fraction (LVEF) and left ventricular diastolic dysfunction (LVDD) were measured using two-dimensional transthoracic echocardiography. The relationship between MBD and LV remodeling and the factors influencing LV remodeling were analyzed.Results One year after KT, MBD was partially improved, mainly characterized by hypercalcemia, hypophosphatemia, hyperparathyroidism, 25-(OH) vitamin D deficiency, elevated bone turnover markers, and bone loss. LVMI, the prevalence of left ventricular hypertrophy (LVH), and the prevalence of LVDD decreased, while LVEF increased. LVH was positively associated with postoperative intact parathyroid hormone (iPTH) and iPTH nonnormalization. ΔLVMI was positively associated with preoperative type-I collagen N-terminal peptide and postoperative iPTH. LVEF was negatively associated with postoperative phosphorous. ΔLVEF was negatively associated with postoperative iPTH. LVDD was positively associated with postoperative lumbar spine osteoporosis. Preoperative LVMI was negatively associated with ΔLVMI and positively associated with ΔLVEF. Advanced age, increased BMI, diabetes, longer dialysis time, lower albumin level, and higher total cholesterol and low-density lipoprotein levels were associated with LV remodeling.Conclusions LV remodeling partially improved after KT, showing a close relationship with MBD.